“Desalinhados”: Brasil, Iugoslávia e Suécia na ONU, 1961-1964 - Espósito, Fábio Adorno (2024)
This work aims to analyze the actions of Brazil, Yugoslavia and Sweden within the scope of the United Nations between the years 1961 and 1964, relating actions and speeches of these three countries to each other and between the two blocs that characterized that Cold War context (CW), during the years in which the “Política Externa Independente” (PEI, “Independent Foreign Policy”) was in force in Brazil. We intend to investigate the similarities and differences, approximations and distances, between the PEI drawn up by Brazil in the period in question, the “non-alignment” policy then constructed and applied by Yugoslavia, and the “neutrality” policy exercised by Sweden, aiming to expand the understanding of the world and the CW beyond the bipolar system closely linked to the perspectives and interests of the superpowers of the time - the United States and the Soviet Union - and their respective blocs, contributing to the construction of a theoretical and historiographical perspective of the period that meets the perspectives and interests of Brazil and the so-called “Global South”. The choice of these three countries is based on the understanding that there are certain intersections in their foreign policy proposals, such as a certain search, at that time, for a relevant and unusual position in the world of non-binding, nor subordination, to the superpowers. We believe it is important to address these three foreign policy experiences, so often relegated to a secondary level by foreign policies and research carried out by members aligned with the Capitalist or Socialist blocs, contributing to a greater understanding of theories, practices and actors, since the Bipolar logic, while making the United States and the Soviet Union main protagonists on the international scene, relegated countries considered “supporting” to a certain shadow